Phytoremediation of arsenic-contaminated soils by arsenic hyperaccumulating plants in selected areas of Enugu State, Southeastern, Nigeria - Prisca Chinenyenwa Onyia (Taylor & Francis Group, 2021)
Under the current study phytoremediation of arsenic from a tropical wetlands and lakes in selected areas of Enugu State was performed. Thirteen soil, plant root and shoot samples used in this research were collected respectively from the Adani Wetlands (six samples), Opi-Agu Lakes (four samples) and control sites (three samples). The plant and soil samples were analyzed in the laboratory using Standard Methods. In the study, As contaminated soils, with maximum As value was observed in Ada Rice Farm 2 (468.0 mg kg−1) followed by Ohuno Wetland 2 (442.0 mg kg−1) and Ada Rice Farm 3 (304 mg kg−1). The highest BCF value (3.31) was recorded in Pteridium Aquilinum root and 1.76 in Ludwigia Erecta shoot, and lowest amount of 0.73 was in Cyperus Exaltatus root and 0.14 in Nymphaea Maculata shoot of As contaminated soils. The translocation factor of As from soil to shoot in the agricultural soils (Adani areas) were found to be in the order of Corrigiola Telephiifolia (1.54) > Ludwigia Erecta (0.57) > Acroccras Amplectens (0.54) > Cyperus Exaltatus (0.45) > Cyperus Imbricatus (0.29) > Nymphaea Maculata (0.14) while in the lake soils (Opi-Agu areas), the translocation factor of As from soil to roots were measured in the order of Sacciolepis Cymbiandra (1.20) > Pteridium Aquilinum (0.53) > Lasimorpha Senegalesis (0.43) > Afromomum Daniellii (0.36). Present research showed that indicated plant species can be used as As accumulator in As polluted soils.